The Khazars as ‘Sons of Abraham’ - Golden, P.B. (Хазарский альманах, 2016)
The accounts of Ibn Sa‘d, Ibn al-Faqîh and al-Tabarî, going back to Hišâm ibn al-Kalbî (late eighth-early ninth century), a contemporary of one of the culminating stages in the conversion of the Khazars to Judaism, are pious legends put forward to claim a link of the Khazars directly to Abraham’s (Arab) descendants in Khurâsân. Although these tales are Arabo-Muslim in origin, it is likely that a connection of the Khazars with Abraham would have found a receptive audience in a Judeo-Khazar milieu The tale also hints at the origins of the qağanal title among the Khazars, giving it a Biblical pedigree and hence sacral authority that would be understandable and acceptable to the Arabo-Muslim world with which the Khazars had developed significant commercial ties. Сообщения Ибн Са‘да, Ибн ал-Факиха и ат-Табари, опиравшиеся на сведения, почерпнутые из трудов Хишам ибн ал-Кальби (ум. ок. 819/820 г.), современника одного из кульминационных этапов принятия хазарами иудаизма, в сущности являются благочестивыми легендами, выдвинутыми для того, чтобы предъявить претензии на непосредственную, родственную связь хазар с (арабскими) потомками библейского Авраама. Несмотря на то, что эти легенды возводятся к мусульманским источникам, выдвинутая ими связь хазар с Авраамом нашла бы восприимчивую публику в иудейско-хазарской среде. Эти легенды также намекают на происхождение каганского титула у хазар, придавая ему библейскую родословную и тем самым сакральный авторитет, приемлемый арабско-мусульманскому миру, с которым Хазария развивала значительные к тому времени торговые связи.